Factors underlying a latitudinal gradient in the S/G lignin monomer ratio in natural poplar variants - Weiwei Zhu; Jin Zhang; Pradeep Kumar Prabhakar; Yen On Chan; Rachel A. Weber; Mengjun Shu; Ganesh Panzade; Connor J. Cooper; Russell B. Davidson; Jin-Gui Chen; Sara S. Jawdy; Jerry M. Parks; et al. (Proceedings of the National Academy of Sciences, 2025)
The chemical composition of wood plays a pivotal role in the adaptability and structural integrity of trees. However, few studies have investigated the environmental factors that determine lignin composition and its biological significance in plants. Here, we examined the lignin syringyl-to-guaiacyl (S/G) ratio in members of a Populus trichocarpa population sourced from their native habitat and conducted a genome wide association study to identify genes linked to lignin formation. Our results revealed many significant associations, suggesting that lignin biosynthesis is a complex polygenic trait. Additionally, we found an increase in the S/G ratio from northern to southern geographic origin of the trees sampled, along with a corresponding metabolic and transcriptional reprogramming of xylem cell wall biosynthesis. Further molecular analysis identified a mutation in a cell wall laccase genetically associated with higher S/G ratios that predominate in trees from warmer lower latitudes. Collectively, our findings suggest that lignin heterogeneity arises from an evolutionary process enabling poplar adaptation to different climatic challenges.